Rodrick rules - Kinney, Jeff (Kinney, Jeff. Diary of a wimpy kid (Series), 2008)
Middle schooler Greg Heffley tells his diary how excited he is to start school this year because his summer vacation was so horrible. In fact, one incident was so terrible that if his older brother Rodrick ever tells anyone, Greg would be the laughing stock of the school. Despite catering to Rodrick's every demand, the embarrassing secret is revealed with surprising consequences.